Adipose-derived stem cell therapies for complex anal fistula: a systematic review and meta-analysis of randomized controlled trials - Zou, Meng; Xue, Mengyao; Liu, Yingjie; Xia, Shijun; Chen, Yongjin; Peng, Zhaoyu; Wu, Wenjiang (Frontiers in Medicine, 2025)
PurposeThis study aimed to systematically investigate the efficacy of adipose-derived stem cells (ASCs) in complex anal fistula treatment.MethodsThis study systematically searched randomized controlled studies on the efficacy of ASCs in treating complex anal fistula published before June 2024 in PubMed, EMBASE, Web of Science, and Cochrane Library. Further, relevant journals were manually searched for relevant references, and two researchers independently performed literature search and screening, data extraction, and bias assessment. Stata version 12.0 was utilized to statistically analyze the healing rate of the anal fistula and the incidence of adverse events.ResultsThis study involved 1,056 patients from five randomized controlled trials, including 561 patients in the treatment group (ASCs/ASCs + fibrin glue) and 495 patients in the control group (fibrin glue/placebo). Meta-analysis revealed better short- and long-term efficacy of adipose mesenchymal stem cell treatment for complex perianal fistulas than in conventional treatment. However, no statistical difference was observed between mid-term and ultra-long-term treatments. Subgroup meta-analysis demonstrated a difference in efficacy between various cell doses. Further, all treatments with different sources of ASCs were superior to conventional quality.ConclusionThis study confirms that Adipose-derived Stem Cells can effectively improve short-term and long-term (1-year) clinical outcomes in patients with complex perianal fistulas, supporting their potential as a novel therapeutic strategy.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024602327.